Utilization of Fuzzy Inference Marketing System for Home Purchase Based on Consumer Interest Using Sugeno Fuzzy Logic - Dedi Mahrizon (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
This study aims to determine the purchase of a house based on consumer interest in accordance with consumer criteria. By using the Sugeno method to determine the input and output variables which are a set of companies, then changing the input variables into a fuzzy set with a fuzzification process, then fuzzy processing manages the data with the minimum method. The last step is to convert the output into a set of deficits with a defuzzification process using the centroid method, so that it will get the desired results on the output variable. This study uses variables Size, Type, Design, Position and Material using mathematical constants or functions of input variables, and in the defuzzification process using the centralized mean method. The results of this study are by using the Sugeno method in fuzzy logic to determine house selection based on consumer interests, fuzzy logic can be used to assist in determining the selection of houses in Solok City and by applying the Sugeno method in fuzzy logic to be able to produce house buying decisions based on consumer interests.